Analysis of Rushdie’S Novel Flory Zogoiby's Demand For Abraham's Firstborn Son In the Moor's Last Sigh: Exploring the Interplay of Fact and Fiction in Rushdie's Novel (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The focal point in thenovel is mixing of fact and fiction which is Rushdie himself in theory. Afterthe haughty arguments exchanged with Aurora and Vasco, Sunil-Nargis coupleleave the 'anti-national gang' of 'the world of art' to be happy on thecommercial side which stresses on the positive side. Next our hero, the Moorgives us a précis of the movie, what it is about and then compares andcontrasts his family to the movies' family. The Moor's Last Sigh is an epicread; it is long and involved and generational. Dozens of characters weave inand out of the story as it paints a picture of their perspective on life- theone they all seem to share. Salman in TheMoor's Last Sigh offers, through his characters, the humorousdefinitions of modem Indian democracy ('one man, one bribe') and the Theory ofRelativity ('everything is for relatives') which shows that there is no finalmorality in affairs of state. When Vasco Miranda leaves for Spain, Aurora getsback to her work, just as politically Mrs. Gandhi returned to power with SanjayGandhi as her right hand and morality gives place to relativity in stateaffairs. Vasco's 'Indian Variation' upon the theme of Einstein's General TheoryD=mc² is a bizarre pun on Indian polity and power. It's well framed by him whoexplains to the young Moor 'Indian variation' upon the theme of Einstein's GeneralTheory: Everything is forrelative. Not only light bends, but everything. For relative we can bend apoint, bend the truth, bend employment criteria, bend the law. D equals mcsquared, where D is for Dynasty, m is for mass of relatives, and c of course isfor corruption, which is the only constant in the universe- because in Indiaeven speed of light is dependent on load shedding and vagaries of power supply.